PEMBUATAN ALAT PANJAT ERGONOMIS UNTUK PEMANENAN BUNGA CENGKEH DENGAN METODE SCAMPER - Herli, Willson Hensky; Widodo, Lamto; Sukania, I Wayan (Jurnal Mitra Teknik Industri, 2024)
As an agricultural country, agriculture in Indonesia is one of the most important economic sectors in the national economy, one of which is clove farming. The research was conducted in a clove tree plantation located in the Purwakarta area. Data collection was carried out by interviews and giving the Nordic Body Map questionnaire to clove farmers. This data collection was aimed at 5 respondents with the aim of finding out complaints and several suggestions from clove farmers. The results of the Nordic Body Map Questionnaire data, the highest rank results were obtained, namely pain in the soles of the left foot and right foot with 3 people answering very painful and 2 people answering painful, to the lowest namely pain in the back, upper waist and lower waist with a total of 4 people answered sick and 1 person answered a bit sick. After obtaining physical complaints with the Nordic Body Map, then carry out REBA analysis to determine the REBA score when farmers climb clove trees and harvest clove flowers. After obtaining the REBA score, the score obtained from climbing clove trees was 8, which means it has a high level of risk and requires investigation and implementation changes to reduce the risk of physical complaints in farmers, while the score from harvesting clove flowers is 12, which means it has a very high level of risk. high and implementation changes are needed to reduce the risk of physical complaints among farmers. For product dimensions, the product dimensions are obtained, namely that the clove tree climbing ladder product has a height of 500 cm. The distance per step is 35 cm. The length of the stair step is 50 cm.